KNOWLEDGE EXPECTATIONS IN THELITERATURE FROM 2020 TO 2024 - Maria del Rosario Molina Gonzalez (IPHO-Journal of Advance Research in Science And Engineering, 2024)
The relationship between personal and group variables are specified with respect to the availability of water supply and management.The paper contributes to the discussion on the management of water resources and services from social variables such as resilience, solidarity and cooperation.In this sense, the parameters for management from the needs of local consumption are set.Under Human Development, the weighting of the needs and water availability is essential for the establishment of an agenda on water management.